The state and religion in post-independence Malaysia: 1957-2016 - Akhmetova, Elmira (2016)
This paper studies the relationship between the state and its dominant religion, Islam, in Malaysia since 1957. When Malaya obtained independence from the British in 1957, Islam has been expected to play a declining role in state affairs. The Constitution guaranteed Islam to be the religion of the state, while religious freedom for non-Muslims should be assured without any discriminations. Since then, Islamic affairs remained under a state responsibility and Malaysia has been hailed for decades as an oasis of moderate Islam. Within last few years, however, some young Malaysians began answering to call from the ISIS fighters. The paper accordingly endeavours to underline the main factors for a decline of moderate and enlightened attitude of Islam in Malaysia. It suggests the politicisation of Islam in the government affairs, combined with the simultaneous authoritarian tactics in policing opposition as one of the main factors for decline in religious freedom. The last part of the paper discusses the external reasons for an intensifying role of political Islam in Malaysian state affairs by highlighting the impact of globalisation, the global ‘War on Terror’ and Islamophobia on wellbeing and security of Muslim communities.